Hair - A Good Source of DNA to Solve the Crime - Mahajan, Vaishali B.; Padale, Vijaya; Kudekar, Deepak Y.; More, Bhausaheb P.; Kulkarni, Krishna V. (Archives of Clinical and Biomedical Research, 2019)
Most often hairs are picked up at the crime scenes and are used as contributing biological evidences in the crime cases. This can be helpful in determining the perpetrators of the crime and providing more information about what happened during the actual incidence. Hairs are commonly encountered in the forensic investigations and can be the good source of DNA. The optimal quantity of template DNA required for PCR based STR Profiling is about 1 ng and sufficient quantity may be present in the root sheath to prove the crime. In the present case, hairs were found in the fist of the deceased and they proved to be an important evidence that linked to the murderer. DNA was extracted from hair roots and profile was generated using PCR based STR Genotyping technology. The DNA profile obtained from the hair root matched with the DNA profile obtained from reference blood of the accused and proved his involvement in the crime.